Synthesis and encapsulation of biocompatible PbS quantum dots passivated with different capping ligands - Alnajjar, Mohammed (2019)
Semiconductor nanoparticles, also known as quantum dots (QDs), have unique properties including stable fluorescence with high quantum yields. These properties are size and composition dependent. QDs are promising candidates for non-invasive deep tissue imaging in the near-infrared wavelength range 700 - 1400 nm in which there is low absorption in biological tissues. In addition, QDs could offer opportunities for anticancer treatments. Currently, available commercial facilities are equipped with charge-coupled device CCD detection with range up to 1000 nm, hence there is a demand for imaging labels for this wavelength range. In this project, new lead sulfide PbS QDs capped with thioglycolic acid (TGA), L-cysteine (L-Cys), L-cysteine methyl ester (L-CysOMe), glutathione (GSH) and TGA/L-CysOMe have been synthesised in aqueous solution. These QDs exhibited good chemical stability and optical emission in the near-infrared region (880 – 950 nm). Also, the diameter of these QDs is 3 – 4 nm, which makes them suitable for encapsulation inside nanocage protein. Among a variety of delivery capsules, apoferritin (AFt) is of particular interest for QD encapsulation. A cysteine-free human heavy chain apoferritin (AFt-) has been expressed and purified to encapsulate the QDs. In order to achieve specific targeting toward cancer cells with human epidermal growth factor receptor 2 (HER2) overexpression, a modified version of AFt- cage with an average of 4 affibody copies (Afb-AFt-) was prepared for the QDs encapsulation. In this project, two types of the synthesised QDs, capped with TGA/L-CysOMe and GSH, were successfully encapsulated separately inside the protein cages, which has not been reported previously. The encapsulation of the QDs was achieved by different routes: altering pH/Urea initiated reassembly/nanoreactor route. The encapsulated QDs in both proteins, AFt- and Afb-AFt-, were prepared with optical and chemical stability. The cytotoxicity of PbS QDs alone and encapsulated in AFt- was examined in vitro by determining the cell viability using the MTT assay. Two types of breast cancer cells were used, MDA-MB-231 (HER2 negative control) and SKBR3 (HER2 positive control). The growth inhibition factor (GI50) values were determined to quantify the cytotoxic effect of the QDs in the cancer cells. The GI50 values of the PbS QDs studied (0.07 mg/mL) decreased in both cancer cell lines following encapsulation in AFt- (0.05 mg/mL) which indicates the higher toxic effect after the encapsulation by the AFt-. The selectivity of the QDs to target HER2 receptors was examined on both cancer cell lines. PbS QDs capped with TGA/L-CysOMe or GSH ligands and their encapsulation were used. The GI50 values decreased when SKBR3 cells were exposed to the Afb-AFt-QDs (0.01 mg/mL) compared to QDs and AFt-QDs (0.1 mg/mL). While the increase in the GI50 values following the encapsulation of the QDs inside the Afb-AFt- indicates a lower level of toxicity in the MDA-MB-231 (0.16 mg/mL). In this project; stable, biocompatible and NIR active PbS QDs capped with TGA/L-CysOMe and with GSH capping ligands were synthesised. The produced QDs were successfully encapsulated into the AFt- and Afb-AFt- capsules. The encapsulated QD solutions are biocompatible, emit in the NIR region and are stable over a period of at least 3 weeks. The delivery and selectivity of the QDs toward specific (HER2-positive) cells were improved by the encapsulation inside the AFt- and Afb-AFt- cages.